Effects of dopamine and domperidone on ventilatory sensitivity to hypoxia after 8 h of isocapnic hypoxia. - Pedersen, M; Dorrington, K; Robbins, P (1999)
Acclimatization to altitude involves an increase in the acute hypoxic ventilatory response (AHVR). Because low-dose dopamine decreases AHVR and domperidone increases AHVR, the increase in AHVR at altitude may be generated by a decrease in peripheral dopaminergic activity. The AHVR of nine subjects was determined with and without a prior period of 8 h of isocapnic hypoxia under each of three pharmacological conditions: 1) control, with no drug administered; 2) dopamine (3 microg. min-1. kg-1); and 3) domperidone (Motilin, 40 mg). AHVR increased after hypoxia (P